Rules of Origin: Regimes in East Asia and Recommendations for Best Practice - Erlinda M. Medalla (Philippine Institute for Development Studies (PIDS), 2008)
With globalization and advances in information and communication technology (ICT) leading to growing international production sharing, amidst the increasing trend in preferential trading arrangements (PTAs), rules of origin (ROO) has been beset with difficult recurring issues. First and foremost is the cost of ROO administration. Second, ROO as part of PTAs could generate new barriers to trade, thus taking with one hand what the other hand has given. In turn, this gives rise to another key concern: its potential use as a protectionist tool. To achieve the East Asian vision of a community, any RTA it would endeavor to establish should set a rational, enabling regime of ROO that would facilitate even as it attempts to prevent trade deflection, with enough safeguards for inclusive development both within and across countries in the region. There is a consensus that the movement should be toward more simple and unrestrictive ROO.
Keywords: 330; rules of origin; regional trade agreement; preferential trading arrangements (PTAs); East Asia; free trade agreements (FTAs); Herkunftsbezeichnung; Regionale Wirtschaftsintegration; Handelspräferenzen; Freihandelszone; Ostasien